VLE of Carbon Dioxide-Loaded Aqueous Potassium Salt of L-Histidine Solutions as a Green Solvent for Carbon Dioxide Capture: Experimental Data and Modelling - Afaf Syalsabila; Abdulhalim Shah Maulud; Humbul Suleman; Nik Abdul Hadi Md Nordin (International Journal of Chemical Engineering)
In this study, vapour-liquid equilibrium of CO2-loaded aqueous potassium salt of L-histidine was studied for a wide range of temperature (313.15–353.15 K), pressure (150–4000 kPa), and solvent concentrations (1–2.5 molar). The experimental results show that L-histidine has an excellent absorptive capacity for carbon dioxide. When compared to conventional solvent (monoethanolamine) and amino acid salt (potassium L-lysinate) at similar process conditions, L-histidine has superior absorption capacity. Moreover, modified Kent–Eisenberg model was used to correlate the VLE of the studied system with excellent agreement between the model and experimental values. The model exhibited an AARE% of 7.87%, which shows that it can satisfactorily predict carbon dioxide solubilities in aqueous potassium salt of L-histidine at other process conditions. Being a biological component in origin, almost negligibly volatile, and highly resistant to oxidative degradation, L-histidine offers certain operational advantages over other solvents used and has a promising potential for carbon dioxide capture.